Consumer Religiosity as a Moderator of the Determinants of Impulse Buying: Discounts and Hedonic Lifestyle - Della Nur Fitriyani; Muhammad Kurniawan; Yeni Susanti (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: Purpose to identify and analyze the relationship between the variables studied. Methodology/approach: This study uses quantitative research methods. the sample was taken from this is april consumers who met certain criteria, such as those who actively bought and had a shopping experience at this is april. In this study the sampling used by researchers is non probability sampling. Data collection techniques using questionnaires and interviews.data sources in this study using primary and secondary data. Results/findings: The results show that discounts and hedonic lifestyle significantly influence impulse buying, with an Adjusted R² of 0.765, indicating that 76.5% of the variation in impulse buying is explained by these variables. Consumer religiosity was found not to moderate the relationship between discounts, hedonic lifestyle, and impulse buying. Conclusion: The study found that although discounts and hedonic lifestyles trigger impulsive buying, consumer confidence serves as a significant moderator, where higher levels of religiosity can reduce such tendencies, providing important insights for Islamic businesses to manage marketing strategies ethically and responsibly. Limitations: This study has limitations on the scope of respondents who only include consumers with a certain cultural background and level of religiosity, so the results may not necessarily be generalized to the wider population. Contribution: This study contributes to enriching the literature on impulsive consumer behavior with a religiosity moderation approach in the context of Islamic business, which is still rarely studied in depth.